Plant communities with the participation of Tulipa tarda Stapf. in Kazakhstan: floristic composition and analysis (Eurasian Journal of Ecology, 2021)
The article presents the results of studies on distribution, ecological preferences and floristic composition of communities with the participation of the rare northern Tian-Shan endemic Tulipa tarda Stapf.  As a result of the analysis of our own materials, data from herbaria, literature and some Internet sources, a point map of the distribution of the species in Kazakhstan was compiled. Based on the descriptions of 13 geobotanical plots, the altitudinal distribution range of the species (1100-1900 m above sea level) was determined, and relative indifference of the species to the steepness and exposure of slopes, as well as its confinement to multicomponent plant communities, mainly of the steppe and semi-steppe type, were established. According to our results combined with two descriptions from the adjacent territory of Kyrgyzstan, the flora of communities with the participation of T. tarda comprises 199 species of higher plants from 140 genera and 45 families. The 16 most species rich families (from Asteraceae to Crassulaceae) comprise 78% of the entire flora of the surveyed communities. The floristic core of the communities consists of only 13 species, most of which are steppe and petro-lithophilic ecological elements. The communities with the participation of Tulipa tarda include eight species listed in the Red Book of Kazakhstan, which stresses the need for special protection of not only of the species under study, but also of all plant communities with its participation.